Infringement of the Barriers of Cancer Via Dietary Phytoconstituents Capsaicin Through Novel Drug Delivery System - Kumar Giri, Tapan; Alexander, Amit; Ajazuddin; Kumar Barman, Tapan; Maity, Subhasis (Current Drug Delivery, 2016)
Cancer is the major cause of fatality and the number of new cases is increasing incessantly. Conventional therapies and existing anticancer agents cause serious side effects and expand the patient’s lifespan by a few years. There is the need to exploit alternative anticancer agents and novel drug delivery system to deliver these agents to the tumor site for the prevention of cancer. Recently, biologically active compounds isolated from plants used for the management of cancer have been the heart of interest. Capsaicin is a major pungent agent present in the chili peppers that is heavily consumed in the world. Capsaicin has demonstrated effectiveness as an anticancer agent, but a restraining factor is its pungency, extremely low aqueous solubility, and poor oral bioavailability which impede its use as an anticancer agent. Many technologies have been developed and applied to conquer this drawback. We bring to light the benefits of this phytoconstituent for treating different types of cancer. We also discussed some of the delivery approaches that have already made an impact by either delivering a drug to target tissue or increasing its bioavailability by many folds.
Keywords: novel drug carrier